PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL PENILAIAN FORMATIF BAHASA INDONESIA PADA KELAS 5 SD - Rr Ratna Andayani; Sandha Soemantri; Sayyidati Marlinda Yunita (PROCEEDING UMSURABAYA, 2024)
This research aims to optimize learning outcomes and active student involvement in Bahasa Indonesia lesson content for class V students at SDN Margorejo 1/403 Surabaya. This research is classroom action research which consists of four stages, namely planning, implementation, observation and reflection. The research subjects were 30 students in class V A of SDN Margorejo 1/403 Surabaya for the 2023/2024 academic year, consisting of 15 male students and 15 female students. The results of the implementation of the action showed an increase in learning outcomes for Indonesian language content by implementing the Problem Based Learning model with a score of 79. 80 and the average class score in cycle 2 was 84. 30. The completion percentage is 97%, which is above the classical achievement percentage set by the school at 80%. Thus, it can be concluded that PBL (Problem Based Learning) learning is considered effective in improving the learning outcomes of Bahasa Indonesia Lesson Content on fairy tales for class V A students at SDN Margorejo 1/403 Surabaya.